PECULIARITIES OF PERSON’ SELF-REALIZATION IN MARITAL RELATIONS - Harutyunyan, N. A. (Արդի հոգեբանություն, 2025)
The article is devoted to the analysis of the process of persons’ self-realization in marital relations. We analyzed the factors of personal self-realization in family life, such as trust, family cohesion, adaptation and satisfaction. As a result, we have established a link between satisfaction with life and self-realization.